Materials spur innovation. (Manufacturing Engineering)
Cutting tool manufacturers are being challenged by new classes of lighter, more abrasive materials as automakers chase government mandated CAFE fuel standards with lighter vehicles. CGI, aluminum alloys, and PM lead the way.